Sociology of the transmigrants in Maghreb:making communities while on the move - (:unkn) unknown (My University, 2006)
North-African countries have become transit countries for migrants coming from sub-Saharan Africa en route to Europe. Our research examines the type of relationship that these persons create with the territory that they cross. From empirical research has emerged the notion of “making communities while on the move”. The members of these communities are tied by links of connivance, complicity and sociation. Meanwhile, they recognise themselves in a given space-time as members of a community. This transnational form of a community - ephemeral but stable despite the turn over of its members- allows multiple systems of memberships, the making of international networks, the crossing of forbidden borders and the by-passing of international agreements. While national, linguistic, cultural identities induce the gathering, facilitate temporary social adjustment as well as passage, they leave the individuals free to join new groups, to develop their own networks that become matter to association and production of ties of a new type. The study has also shown how women, thanks to their motherly capacities, make mobility invisible and how the family hierarchical order can be transformed during transmigration.
Keywords: African Research